Anxiety and nonpsychotic mental disorders in acute urticaria - Eli Magen; Eugene Merzon; Shai Ashkenazi; Abraham Weizman; Iris Manor; Israel Magen; Avi Yakov; Akim Geishin; Ilan Green; Avivit Golan-Cohen; Shlomo Vinker; Ariel Israel (Brain, Behavior, & Immunity - Health)
Background: Acute urticaria (AU) is characterized by the sudden onset of wheals, angioedema, or both, with symptoms resolving within 6 weeks. While the association between chronic urticaria and mental health disorders is well-documented, the relationship between AU and psychological conditions remains understudied. Objective: To investigate the association between AU and anxiety and personality disorders, and to explore the potential psychoneuroimmunological mechanisms underlying these relationships. Methods: We conducted a population-based case-control study using the comprehensive electronic health records database of Leumit Health Services in Israel. The study included 72,805 AU patients and 291,220 matched controls. Subjects were matched for gender, age, ethnicity, year of first documented visit, and socioeconomic status. We analyzed the 20-year prevalence of anxiety disorders, personality disorders, and various nonpsychotic mental disorders in both groups. Results: AU patients demonstrated significantly higher prevalence of anxiety disorders (7.02 % vs. 5.22 %, p < 0.001, OR = 1.37 [95 % CI: 1.33–1.42]), personality disorders (0.23 % vs. 0.134 %, p < 0.001, OR = 1.73 [95 % CI: 1.44–2.08]), and adjustment disorders (0.91 % vs. 0.67 %, p < 0.001, OR = 1.37 [95 % CI: 1.25–1.50]) compared to controls. Particularly notable were the associations with personality disorders characterized by persistent mood disturbances (OR = 1.91 [95 % CI: 1.53–2.38]) and adjustment disorders with depressive features (OR = 1.49 [95 % CI: 1.27–1.74]). Conclusions: Our findings reveal significant associations between AU and various mental health disorders, particularly anxiety and personality disorders. These associations suggest a complex bidirectional relationship mediated through psychoneuroimmunological pathways involving the HPA axis, mast cell activation, and inflammatory cytokines. We recommend implementing specific screening tools (HADS, GAD-7) and a stepped-care approach for integrated dermatological and psychological management of AU patients.